Implementasi Perencanaan Pendidikan Dakwah Islam - Abd. Hakim (MODELING: Jurnal Program Studi PGMI, 2021)
Planning Islamic da’wah education is the process of compiling actions to be carried out in order to achieve the expected goals of Islamic education. The preparation process must also be based on the basic values of Islamic teachings, namely based on the Qur'an and Al-Hadith. The purpose of this research is to explain the implementation of Islamic da’wah education planning. The method in this study uses a qualitative method with the type of descriptive analytic research. The results of this study indicate that the planning of Islamic da'wah education is one of the implementations of God's commands, which is to call people towards Islamic teachings which include issues of theology, sharia, morals, and institutions. Islamic da'wah education planning is a systematic thinking pattern in determining everything that will be carried out in order to achieve a goal, while the function of Islamic da'wah education planning is to determine the goals or framework of actions needed to achieve certain goals.